2010
DOI: 10.1039/c0cp00541j
|View full text |Cite
|
Sign up to set email alerts
|

Model anodes and anode models for understanding the mechanism of hydrogen oxidation in solid oxide fuel cells

Abstract: This article presents a literature review and new results on experimental and theoretical investigations of the electrochemistry of solid oxide fuel cell (SOFC) model anodes, focusing on the nickel/yttria-stabilized zirconia (Ni/YSZ) materials system with operation under H(2)/H(2)O atmospheres. Micropatterned model anodes were used for electrochemical characterization under well-defined operating conditions. Structural and chemical integrity was confirmed by ex situ pre-test and post-test microstructural and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
156
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 54 publications
5
156
3
2
Order By: Relevance
“…The effect of the TPB density on the electrochemical activity of the surface is very pronounced and a length-specific activity of 0.00014 S/cm or 7000 cm can be estimated. For comparison, Ni-YSZ anodes typically exhibit 10-100 times lower TPB activity 45 at the same temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the TPB density on the electrochemical activity of the surface is very pronounced and a length-specific activity of 0.00014 S/cm or 7000 cm can be estimated. For comparison, Ni-YSZ anodes typically exhibit 10-100 times lower TPB activity 45 at the same temperature.…”
Section: Resultsmentioning
confidence: 99%
“…27 Reaction mechanism and kinetics.-There have been many studies on the mechanism and kinetics for the HOR of Ni and Ni-YSZ cermet electrodes. [20][21][22][23][24]28 In moist H 2 , the impedance responses of the Nibased electrodes show the existence of one or more (up to three) arcs, [20][21][22]28 indicating the contribution of several reaction steps to the overall hydrogen oxidation reaction. Our early studies show that the electrode process for the HOR can be described by two electrode steps associated with low and high frequency arcs; the electrode process associated with low frequency arc has been attributed to hydrogen dissociation adsorption/diffusion on the surface of Ni, and the one associated with high frequency arc is the process of hydrogen transfer from the Ni/YSZ surface to the TPB region, followed by the charge transfer process at TPB.…”
Section: Effect Of Temperature-mentioning
confidence: 99%
“…18,19 The mechanism and kinetics of the hydrogen oxidation reaction (HOR) on Ni and Ni-YSZ cermet electrodes have been extensively studied. [20][21][22][23][24][25][26][27] Mizusaki et al studied HOR on nickel patterned electrode on YSZ electrolyte and found that the rate of anodic reaction was essentially determined by the reaction of hydrogen and the adsorbed oxygen on the nickel surface. 26, 28 Primdahl and Mogensen 29,30 studied the HOR on Ni-YSZ cermet anodes by impedance spectroscopy and the results indicate that the performance of the anodes critically depended on the cermet structure.…”
mentioning
confidence: 99%
“…This combination suggests that hydrogen electro-oxidation may be rate-limited by elemental processes involving bi-molecular hydrogen species, such as adsorption or dissociation of H 2 on oxide surfaces. 25,26 In addition to lowering the overall electrochemical reaction resistance, application of Pt particles decreases the pH 2 sensitivity of R electrode , suggesting that the catalyst enhances the rates of these steps to such an extent that the rate-determining process may no longer involve the H 2 molecule. This possibility is consistent with observations in the literature that Pt is highly active for H 2 adsorption/ dissociation reactions.…”
mentioning
confidence: 99%